Low-carbohydrate diets for type 1 diabetes mellitus: A systematic review. - Jessica L Turton; Ron Raab; Kieron B Rooney (PLoS ONE)
Type 1 diabetes is an autoimmune condition characterised by pancreatic beta cell destruction and absolute insulin deficiency. The strongest predictor of diabetes complications is glycaemic control and achieving HbA1c ≤ 7.0% is the primary management target. However, standard treatment appears to be lacking and adjunctive strategies require consideration. A systematic review was conducted to examine the effect of low-carbohydrate diets on type 1 diabetes management. Four databases were searched from inception until 28 March 2017: MEDLINE; CINAHL; Cochrane Library; and EMBASE. All primary studies containing a methods section (excluding cross-sectional) were included. Reports had to quantitatively measure the effect(s) of a dietary intervention or observed intake over at least two weeks where carbohydrate is below 45% total energy in adults and/or children with type 1 diabetes. The primary outcome was HbA1c and secondary outcomes were severe hypoglycaemia, total daily insulin, BMI, quality of life and mean daily glucose. Seventy-nine full-text articles were assessed for eligibility and nine were included (two randomised controlled trials, four pre-post interventions, two case-series, one case-report). Eight studies reported a mean change in HbA1c with a low-carbohydrate diet. Of these, four reported a non-significant change (P ≥ 0.05) and three reported statistically significant reductions (P < 0.05). Two studies reported severe hypoglycaemia, five reported total insulin, three reported BMI, and one reported blood glucose. Due to the significant heterogeneity of included studies, an overall effect could not be determined. This review presents all available evidence on low-carbohydrate diets for type 1 diabetes and suggests an urgent need for more primary studies.